REPRODUCTIVE DISORDERS CAUSED BY Toxoplasma gondii IN SHEEP - Consalter, Angélica ntonio Ribeiro; Silva, Andressa Ferreira da; Motta, Adriana Costa da; Ferreira, Ana Maria Reis (Arquivos de Ciências Veterinárias e Zoologia da UNIPAR, 2016)
Toxoplasma gondii is a cosmopolitan, intracellular, obligatory parasite protozoan of importance to public and animal health. In sheep, this species is a causative agent of reproductive disorders. The main sign produced by T. gondii infection in this species is abortion, which causes economic losses to sheep ranching. The main purpose of this review is to summarize the abortion outbreaks and reproductive disorders caused by T. gondii infection in sheep, also addressing aspects of biology, diagnosis, prevention and control of the parasite.